Hemispheric asymmetry of [11C](R)PK11195 binding to translocator protein 18 kDa (TSPO) in normal brain - Alfaifi, Bandar Q.; Tuisku, Jouni; Matilainen, Markus; Anton-Rodriguez, Jose; Lewis, Daniel; Jackson, Alan; Coope, David J.; Airas, Laura; Deakin, Bill; Herholz, Karl; Gerhard, Alexander; Hinz, Rainer (SAGE, 2025)
Many positron emission tomography (PET) imaging studies in health and disease of the translocator protein 18 kDa (TSPO) using different radioligands have been published, however, only few separately reported left and right regions of interest in the brain. Thus, TSPO binding in healthy brains using [11C](R)PK11195 datasets of 76 participants from two PET sites was assessed for symmetry. Structural MRI scans were used for brain segmentation and to define six regions of interest (thalamus, putamen, temporal, frontal, parietal, and occipital cortex) with a probabilistic brain atlas. The simplified reference tissue model with bilateral grey matter cerebellar reference tissue input function was used to estimate distribution volume ratios (DVR). On a global level, the right hemisphere had higher DVR than the left side (p < 0.001, Cohen's d = 1.14 for grey matter and 1.17 for grey matter and white matter regions of interest). There were statistically significantly greater DVRs in all right regions with p < 0.001 except in the occipital cortex (p = 0.012, Cohen's d = 0.29). This asymmetry was independent of age, sex, and handedness evaluated using a linear mixed-effects model. These results demonstrate that [11C](R)PK11195 has an asymmetric binding distribution in the human brain, which needs to be accounted for in clinical studies.